CHARACTERIZATION STRUCTURE MICRO OF GRAPHENE OXIDE WHICH SYNTHESIS FROM BAGASSE WITH MODIFIED HUMMERS METHOD - viola sesri wahyuli; - Ramli (PILLAR OF PHYSICS, 2021)
This study aims to form a graphene oxide layer from bagasse, which by knowing the microstructure of the layer graphene oxide can be used as microwave absorption. In the process, bagasse is made into activated carbon with various carbonation temperatures, namely 300oC, 350oC, 400oC and 450oC. Then it was synthesized using the modified hummers method by mixing carbon with H2SO4, KMnO4, H2O2 and aquades. Then they were characterized using FTIR, XRD and SEM.Based on the FTIR data, it states that there is a relationship between carbon (C), hydrogen (H) and oxygen (O) which proves the formation of a graphene oxide layer. Also based on the results of XRD which states that the diffraction angle is in the range of 10o-90o and has the highest crystal size of 40.5267076 nm. Likewise, the results from SEM which stated that the best graphene oxide was at an average particle size of 81,4043598 nm. The resulting graphene oxide is also shaped like monolayer sheets.